A new acoustic emission descriptor for modelled sources of partial discharges - F. Witos; Z. Gacek; A. Opilski (Archives of Acoustics, 2002)
Partial discharges (PD) generated by differently modelled PD sources have been studied by the acoustic emission (AE) method. The results obtained were compared with the measured apparent electric charge values. Acoustic images of the PD phenomena were created by recorded waveforms, phase diagrams, frequency characteristics and calculated amplitude distribution diagrams. Basing on the amplitude distributions, a new AE descriptor --- the ADP descriptor (Amplitude Distribution of Power of AE signal descriptor) was evaluated. The ADP descriptor distinguishes the physical processes connected with the PD. For the described measuring situations, the calculated values of the ADP descriptor show a good correlation of the ADP descriptor values with the value of the apparent electric charge.